Wage and Test Score Dispersion: Some International Evidence - Kelly Bedard; Christopher Ferrall (Luxembourg Income Study (LIS), 1997)
This paper includes fifty observations on wage distributions across eleven countries and two age cohorts defined by international mathematics tests given to thirteen-year-olds in 1962 and 1982. It is found that wage dispersion later in life is never greater than test score dispersion. In particular, Lorenz curves for a cohort's wages always lie above or on top of the cohort's test score Lorenz curve. Wage dispersion, as summarized by Gini coefficients, is significantly related to test score dispersion and union density in the country. A general fall in test score dispersion between 1962 and 1982 appears to be reflected in reduced wage dispersion. For three countries with available data (the U.S., the U. K., and Japan), evidence of skill-based changes in wage dispersion between the early 1970s and the late 1980s is found.
Keywords: 330; Einkommensverteilung; Lorenz-Kurve; Welt